Analisis manajemen strategi teknologi digital terhadap bisnis makanan viral dan ketertarikan pelanggan : Studi kasus UMKM di Kota Malang - ahady, ahmad auly (Maliki Interdisciplinary Journal, 2025)
Technological advancements have revolutionized the way we work, communicate, and transact, enhancing efficiency and effectiveness in the business world. This innovation also expands business reach and facilitates the discovery of new target markets, especially among the younger generation who actively use gadgets and follow social media trends. Many of them leverage viral trends as a source of income, driving the growth of micro, small, and medium enterprises (MSMEs) in the culinary sector. Digital marketing has become key for MSME players to promote products effectively and efficiently, saving costs and time. This research shows that although business experience has a negative impact on sales if not accompanied by innovation, a combination of good experience and viral promotion strategies can significantly boost sales. Therefore, MSME players are advised to utilize technology and digital marketing to adapt to market changes and meet the ever-evolving consumer needs.